Bullying y su incidencia en la conducta suicida en un adolescente de 15 años del cantón Vinces - Avellán Guin, Natalia Valentina (2022)
The present case study was developed with a problem of suicidal behaviors in a adolescent from the Province of Los Ríos in the Vinces Canton. The symptoms reflected by the adolescent have been presented with greater incidence in the cognitive area due to distorted thoughts that affect him in his social environment. In the collection of information, techniques such as the semi-structured interview, clinical history and the Beck depression inventory test were used to obtain a presumptive diagnosis, in addition, techniques of the cognitive behavioral model were applied, which helped to detect distorted thoughts of the patient to modify these thoughts, being these techniques of cognitive restructuring.